Optimalisasi Produk Unggulan Kawasan Kuliner Kelurahan Ledok, Kecamatan Argomulyo Kota Salatiga - Yustina Denik; Julian Andriani Putri; Tri Maryani (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This service aims to develop and promote the potential of culinary tourism in Argotelo, a culinary place in Salatiga City, Indonesia. This research involves market analysis, facility improvements, menu diversification, and promotional efforts to increase awareness and tourist visits. The results include increased sales turnover, increased visitor numbers, product diversification and a positive impact on local communities. This dedication stimulates local economic growth and creates a better culinary experience for visitors. The success of this service shows the importance of developing and promoting culinary tourism potential in the area..